2015
DOI: 10.1007/bf03399419
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the Swiss Franc Real Exchange Rate

Abstract: a The authors are very grateful to Bruno Parnisari and Peter Steiner (SECO) for supplying previously unavailable data on Swiss sectoral value added, as well as to Gian Maria Milesi Feretti (IMF) for placing his international data set on net foreign assets at our disposal and Richard McKenzie (OECD) for valuable data suggestions. We also wish to thank Thomas Moser, Ulrich Kohli, Michel Peytrignet, Luca Ricci as well as participants to SNB internal seminars for helpful discussions. Finally we thank two anonymous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…As in Gubler and Sax (2011), Fischer and Hossfeld (2014) and Mancini Griffoli et al (2015, the dependent variable of our BEER model is the bilateral RER. This choice presents the advantage that the RER captures relative prices in a cleaner fashion than the REER, since it is unaffected by changes in trade weights, which in turn can be endogenous to exchange rate variations as they modify the relative value of trade flows across partners.…”
Section: The Dependent Variablementioning
confidence: 99%
“…As in Gubler and Sax (2011), Fischer and Hossfeld (2014) and Mancini Griffoli et al (2015, the dependent variable of our BEER model is the bilateral RER. This choice presents the advantage that the RER captures relative prices in a cleaner fashion than the REER, since it is unaffected by changes in trade weights, which in turn can be endogenous to exchange rate variations as they modify the relative value of trade flows across partners.…”
Section: The Dependent Variablementioning
confidence: 99%
“…Our empirical specification considers some variables suggested by the literature as relative price determinants, among which is productivity. A well-established result in the literature is the so-called Balassa (1964)-Samuelson (1964 mechanism, which states that relatively larger increases in productivity in the traded goods sector in a country should be associated with a REER appreciation of the currency of that country (Candelon et al 2007;Galstyan and Lane 2009;Griffoli et al 2015). As far as the TOT is concerned, a common view in trade and growth theory is that it should deteriorate after a rise in the supply of domestic goods since the increased domestic supply could be absorbed by international markets at falling prices.…”
Section: Datamentioning
confidence: 99%
“…Theory suggests that a fiscal devaluation will exert its effects by affecting the TOT and the REER. However, even if an extensive literature has investigated the economic determinants of both the TOT and the REER (Corsetti et al 2007;Monacelli and Perotti 2008;Galstyan and Lane 2009;Griffoli et al 2015), only a few papers have focused on the relationship between specific taxes and relative prices (Alesina and Perotti 1995; Freund and Gagnon 2017), and little is known on the potential impact of a fiscal devaluation. Tkalec et al (2019) studied the impact of both VAT and SSCs' tax changes on the real exchange rate, but do not specifically analyse a revenue-neutral tax shift.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, the significance of each factor varies among all countries in the short run. Using the annual data from 1973 to 2011 Griffoli et al (2015) investigated the determinants of Swiss franc. The main findings indicated that trade openness and the government spending are the key determinants in the long run.…”
Section: Literature Reviewmentioning
confidence: 99%